Impact of the implementation of electronic consultation in outpatient care for patients with cardiovascular disease in a Cardiology Service of a tertiary hospital. (3rd October 2022) - Mazon Ramos, P; Rey-Aldana, D; Alvarez Alvarez, B; Portela Romero, M; Garcia Vega, D; Agra Bermejo, R; Rigueiro Veloso, P; Espasandin Dominguez, J; Gude Sampedro, F; Cinza Sanjurjo, S; Gonzalez Juanatey, J R
Abstract:  : The main objective of health systems is to organize health care in a universal way, by including the population as a whole, cost-effectively, and incorporating care methodologies that allow personalized health care (1). The integrated electronic medical records between levels of care allows non-face care modalities such as electronic consultation. In it, a health professional, most commonly a General Physician, consults with a Hospital doctor through a computer system in which the clinical history is housed, allowing part of the health care to be resolved without displacement of the patients (2). Despite the growing implementation of telematic consultation models and the recommendations to regularly evaluate the quality of care, to ensure patient safety and the best possible diagnosis and treatment practices in telemedicine (3). This aspect acquires a special relevance in the case of patients with an established diagnosis of cardiovascular disease since an e-consultation through the electronic medical record could be less efficient than a face-to-face consultation, in identifying symptoms and clinical signs of alarm and compromise in some cases its clinical evolution. Purpose: To evaluate the clinical impact of the introduction of an electronic consultation in the ambulatory care model of a Cardiology Service to patients with an established diagnosis of cardiovascular disease, comparing it with a face-to-face single act consultation model. Methods: The epidemiological and clinical data available from the 47, 337 patients referred from January 1, 2010 to December 31, 2019, to the Cardiology Service of a health area were recorded, in which all physicians share the same electronic medical record. Patients with cardiovascular disease were considered if they had a history of ischemic heart disease, heart failure, peripheral arterial disease and ischemic cerebrovascular disease. The number of visits to the emergency room, the number of admissions due to cardiovascular causes and mortality were analyzed as events of interest during the first year after attending the Cardiology Service. Results: Patients without CVD were resolved more frequently in the e-consultation (24.8% vs 11.3%, p<0.001) and patients with CVD required more follow-up consultations (69.8% vs 40.8%, p<0.001). The analysis of time trends showed that since the implementation of the e-consultation, waiting times were reduced in a similar way in both analysis groups (p<0.001) and, in addition, there was a decrease in emergency services assistance (p<0.001) and in mortality (RR: 0.78 [CI95%: 0.65–0.95], p<0.001), Figure 1; and a stabilization in admissions (RR: 0.95 [CI95%: 0.87–1.04], p<0.001), Figure 2 Conclusions: The introduction of an e-consultation in the outpatient management model of referrals for consultation to a cardiology service is effective in reducing waiting time and is safe, since it reduces mortality in patients with cardiovascular disease. Funding Acknowledgement: Type of funding sources: None.